Violência estrutural e o "tráfico de drogas" : as influências no atendimento às famílias na política de assistência social - Bitencourt, João Vitor (2019)
This study aims to analyze the social experiences of families assisted and / or accompanied by PAEF and PAEFI, who suffer from the influence of structural violence in the context of "drug trafficking" in the city of Porto Alegre, ) users, professionals and managers. The specific objectives were: a) To analyze the understanding of the PAIF and PAEFI professionals on structural violence in the context of "drug trafficking"; b) Search how CRAS and CREAS materialize their actions, amidst the influences of structural violence in the context of "drug trafficking", with the families that access the programs / services; c) Analyze how "drug trafficking" influences the dimension of socio-territorial arrangements and configurations, in the accompaniments to the families in PNAS; d) Identify the determinants of gender, race / ethnicity, social class and generation associated with "drug trafficking" in PNAS service territories. The CRAS and CREAS of this municipality were defined as Universe and as subjects of research the managers, professionals and users in the Lomba do Pinheiro and Eixo-Baltazar regions, being characterized as being an intentional sample. For the professionals, managers and managers of the family groups, we used semi-structured individual and collective interviews and focus groups. A documentary analysis of studies and documents was also carried out to indicate the diagnosis and / or appraisal of the phenomenon of structural violence and "drug trafficking", such as social WELFARE policy: atlas of Violence 2017-2018; Drug Law 11,343 / 2006; NOB-RH / SUAS; guidelines of PAIF and PAEFI. We also opted for the technique of unsystematic observation, recorded through field diaries. Twelve professionals, five users and one trainee participated, totaling 18 subjects. The content analysis of Bardin (1977) was adopted. The study revealed that "drug trafficking" is a multidimensional phenomenon in the context of structural violence. It interferes, due to the prohibition of drugs and the criminalization of territories and segments, in different ways in the daily lives of families residing in the social welfare territories. "Drug trafficking" is perceived as an illegal activity and as a way of life, and also sometimes as a transmission of values and the internalization of rules. The professionals are exposed to situations of risk and insecurity, resulting in the interventional immobility and / or creation of reflexive-constructive proposals with the population. The professionals consider that many families have direct or indirect connection with trafficking, but few speak about it, whether due to fear, myths (stigmas and stereotypes) or the naturalization of this phenomenon in the territory. This situation stands out in a secondary way in everyday work, not being characterized as an initial demand. It is emphasized the importance of this public policy as a research space on the theme in terms of intersectoral work, to problematize the "criminalizing process" towards creating reflections on the articulation between the subjects, fundamental in the daily life of institutions: in the collective welcome , in the spaces of groups and workshops, in community actions, in articulation with constitutive services such as PROJOVEM, SCFV, Microrrede and Forums, as well as in external environments such as collectives and movements to deal with violence. There are relations of force, between different perspectives and objectives, regarding worldviews, ideologies and political projects around structural violence in the context of drug trafficking. In the case of families forced to move from territory - harmful situation to family and community ties, the professionals have few support mechanisms (some decisive and deep for the family experience), in the face of serious situations. The interventions are based on aid for the rapid change of the family of territory, neighborhood or city, depending on the risk of violence. The Program for the Protection of the Child and Adolescent Threatened of Death (PPCAAM) was highlighted in order to preserve the lives of children and adolescents threatened with death. Urges the need to operationalize forms of permanent education, considering the particularities of each territory, promoting inquiries that value socio-family matricity through a gender and race/ethnicity perspective in the intersectional character, given the contradictions assumed about the mode and condition of life of the woman from the periphery, seen as the main responsible for the care of the family. It is concluded that it is urgent to question the character of naturalization of the immutable reality around this problem, aiming at the creation of proposals and strategies that can transform the realities of violence and social inequality.